Weed Response to Different Tank-Mix Herbicide Combinations and its Impact on Winter Rice Performance in Zero Till Non-Puddled Condition - Islam, A K M Mominul; Said, Md Abu; Rhaman, Mirfatun; Jahan, Israt; Yeasmin, Sabina; Hasan, Mahmudul; Motmainna, Mst; Anwar, Md. Parvez (Fundamental and Applied Agriculture, 2024)
Tank-mixture of two or more chemical groups of either pre- or post-emergence herbicide might play a vital role to manage weeds of a diversified community more effectively than their single or sequential application. Although some proprietary herbicides are available in the market, their number is very limited. The aim of this research was to evaluate the weed response to different tank-mix pre- or post- emergence herbicide combinations and its impact on winter rice performance in zero-till non puddled transplanted condition. Twenty-one treatments were used in each experiment (either pre- or post-emergence herbicide). Treatments comprised six pre-emergence herbicides with their 13 tank-mix combinations (at a ratio of 1:1), one proprietary pre-emergence herbicide and a season-long weedy plot as control. Similar treatments combination was also considered for post-emergence herbicide. Both the experiments were conducted under RCB design with three replications. Sole application of Triafamone pre-emergence herbicide performed as the best in terms of weed control efficiency (%) and yield increase over control (%) followed by Triafamone + Pretilachlor and Triafamone + Pendimethalin. In case of tank-mix post-emergence herbicide Pyrazosulfuron-ethyl+ Penoxsulam performed as the best in terms of weed control efficiency (%) and yield increase over control (%) followed by sole application of post-emergence Penoxsulam. Tank-mixture of Triafamone + Pretilachlor or Triafamone + Pendimethalin pre-emergence herbicide or Pyrazosulfuron-ethyl+ Penoxsulam post-emergence herbicide at a ratio of 1:1 might be the perfect alternative to sole or sequential application of herbicide for effective weed control and to obtain higher rice yield.